DEVELOPING CRITICAL THINKING SKILLS THROUGH ENGLISH LANGUAGE LEARNING - Norboboeva Saida Azamatovna (Web of Journals Publishing, 2024)
In today’s interconnected world, critical thinking has become a cornerstone of effective communication and problem-solving. English language learning, beyond its linguistic benefits, provides a unique platform for cultivating critical thinking skills. This article explores the integration of critical thinking activities in English language classrooms and their impact on learners’ overall cognitive development.
Keywords: Critical thinking, English language learning, Socratic questioning, problem-solving, education strategies.